Food Preferences and Nutritional Status: Insights on Nutrition Transition in University Community - Rana, Zahwa Arshad; Ahsan, Muhammad; Ali, Muazzam; Atif, A.; Uzair, Muhammad (Universitas Pendidikan Indonesia (UPI), 2022)
'Nutritional transition' usually entails a move towards a high-energy diet and lower levels of practice with detrimental effects. The pilot research examined whether parent education works at the home level in a small group of University employees to affect food adoptions and child nutrition. Three groups of people with different degrees of skills and education participated. In all homes, weighed food records were used to determine the per capita intake. Nutrient calculators were used to determining the nutrients. Children were classified into underweight, overweight, and normal weight using BMI scores. A total of 178 individuals were present in the research, which provided us with food log data. There were 67 children from 30 households (32 (47.8%) were girls and 35 (52.2%) were males). The age of children with median age is 5.52 Â± 2.89 years. Research revealed that 43.3% of children were underweight and 25.4% were overweight by using their BMI scores. Energy consumption was higher in families with overweight children compared to families with underweight and normal children. Underweight kids come from impoverished families. The per capita consumption of the whole family in children was strongly linked with the BMI. Obesity has risen among families with medium incomes belonging to Class 2â€”probably in families that move up from poverty. The nutritional condition of children was largely linked with motherly education.